PERAN MEDIA SOSIAL SEBAGAI SARANA PROMOSI PADA PEMASARAN HASIL PENGOLAHAN AMPLANG DI KECAMATAN SANGA SANGA KABUPATEN KUTAI KARTANEGARA - Rahmasari; Gusti Haqiqiansyah; Qoriah Saleha (2339-1324, 2020)
The aim of this study is to determine the level of producers perception in using social media as a means of promotion and determine the role of social media as a means of promotion of marketing envelopes. The research method used was a survey method, quantitative and qualitative data analysis techniques with a total sample of 11 people. The results of this study indicate that the producers perception of social media is in the medium category, with a score reached 27,91 which is in the range of scores of 20,01 – 28,00. Based on index value (%) shows a score of 82,75 which is in the range of 66,68-100 which is included in the agreed category, meaning that social media for promotion tool for marketing amplang in Sanga-Sanga District is plays a role to marketing promotion Keywords: Role of Social Media, Promotion, Amplang